CASE STUDY OF AN INDONESIAN LANGUAGE-BASED EDUCATIONAL APPROACH - Ertinawati, Yuni; A, Disti Citra Maudina; Subekthy, Ginna Febriana; Qoriatin, Soleha (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to provide education regarding the good and correct use of Indonesian in class 1A. Humans are social creatures who definitely interact with each other, one of the media we as humans interact with is language. As Indonesian people, we should use Indonesian, especially good and correct Indonesian. This research was conducted offline while studying citizenship courses. The purpose of this research is to provide education to readers about how important it is to speak good and correct Indonesian, especially the use of good and correct Indonesian in class 1A. Judging from the good and correct use of Indonesian in class 1A, only 60% of individuals are aware of the importance of speaking good and correct Indonesian. Even though all students listen carefully when learning Indonesian language courses, there are still many students who use their respective regional languages.